TEACHING ANXIETY IN PRE-SERVICE TEACHERS DURING MICROTEACHING CLASS - Putri Rati Ningsih; Titin Rahmiatin; Syarif Amin (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study examines the factors that contribute to teaching anxiety and the coping strategies employed by pre-service teachers during microteaching sessions. The research adopts a qualitative method with a narrative research design, involving nine pre-service teachers from Universitas Muhammadiyah Kendari. Data were collected through semi-structured interviews and analyzed using a thematic analysis approach. The findings reveal that teaching anxiety stems from both internal factors, such as low self-confidence, fear of making mistakes, and limited teaching experience, and external factors, including peer and lecturer evaluations, time constraints, and large class sizes. To manage these anxieties, pre-service teachers employed various coping strategies, including thorough preparation, positive self-talk, reflection, and seeking social support. Peer encouragement and constructive feedback from lecturers played a crucial role in reducing anxiety and enhancing teaching readiness. The study suggests that teacher education programs should foster not only pedagogical competence but also emotional resilience. Future research is recommended to explore structured interventions to mitigate teaching anxiety in practical teaching contexts.